Shared Decision Making in Practice and the Perspectives of Health Care Professionals on Video-Recorded Consultations With Patients With Low Health Literacy in the Palliative Phase of Their Disease - Roodbeen, Ruud T. J. (MDM Policy Pract, 2021)
Introduction. An important goal of palliative care is improving the quality of life of patients and their partners/families. To attain this goal, requirements and preferences of patients need to be discussed, preferably through shared decision making (SDM). This enhances patient autonomy and patient-centeredness, requiring active participation by patients. This is demanding for palliative patients, and even more so for patients with limited health literacy (LHL). This study aimed to examine SDM in practice and assess health care professionals’ perspectives on their own SDM. Methods. An explanatory sequential mixed methods design was used. Video recordings were gathered cross-sectionally of palliative care consultations with LHL patients (n = 36) conducted by specialized palliative care clinicians and professionals integrating a palliative approach. The consultations were observed for SDM using the OPTION(5) instrument. Potential determinants of SDM were examined using multilevel analysis. Sequentially, stimulated recall interviews were conducted assessing the perspectives of professionals on their SDM (n = 19). Interviews were examined using deductive thematic content analysis. Results. The average SDM score in practice was moderate, varying greatly between professionals, as shown by the multilevel analysis and by varying degrees of perceived patient involvement in SDM mentioned in the interviews. To improve this, professionals recommended 1) continuously discussing all options with patients, 2) allowing time for patients to talk, and 3) using strategic timing for involving patients in SDM. Discussion. The implementation of SDM for people with LHL in palliative care varies in quality and needs improvement. SDM needs to be enhanced in this care domain because decisions are complex and demanding for LHL patients. Future research is needed that focuses on supporting strategies for comprehensible SDM, best practices, and organizational adaptations.